Composite catalyst as well as preparation method and application thereof

By using a composite catalyst composed of β molecular sieve and a cobalt-based catalyst, the problem of difficult to obtain both high CO conversion and high selectivity of marine coal in Fischer-Tropsch synthesis is solved, and the effect of high selectivity of marine coal preparation at low temperatures is achieved.

CN119608229AActive Publication Date: 2025-03-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311173292.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-12
Publication Date
2025-03-14
Estimated Expiration
2043-09-12

AI Technical Summary

Technical Problem

The existing Fischer-Tropsch synthesis technology has the problem of having high CO conversion rate and high selectivity for aircraft coal in high selectivity preparation, and the reaction temperature is relatively high, making it difficult to achieve high selective synthesis at low temperatures.

Method used

A composite catalyst is used, which consists of β molecular sieve and a cobalt-based catalyst, which includes zirconium oxide and cobalt. By adjusting the ratio and preparation method of the composite catalyst, the ratio, proximity and synergistic mechanism of metal active position to acidic position are changed.

Benefits of technology

High selective preparation of aircraft coal is achieved at 220°C, taking into account high CO conversion and high aircraft coal selectivity, and improving the performance of the catalyst, especially the selectivity of aircraft coal under low temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608229A_ABST
    Figure CN119608229A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalysts, and discloses a composite catalyst and a preparation method and application thereof.The composite catalyst comprises a molecular sieve and a cobalt-based catalyst, on the basis of the total amount of the composite catalyst, the content of the molecular sieve is 2-35 wt%, the content of the cobalt-based catalyst is 65-98 wt%, the cobalt-based catalyst comprises zirconium oxide and cobalt, and the cobalt-based catalyst comprises zirconium oxide and cobalt. On the basis of the total amount of the cobalt-based catalyst, the content of cobalt element is 5-35 wt%, and the content of zirconium oxide is 65-95 wt%; based on the total amount of zirconium oxide, the content of zirconium oxide existing in a monoclinic phase form is more than 50%. When the composite catalyst provided by the invention is applied to Fischer-Tropsch synthesis, high CO conversion rate and high aviation kerosene selectivity can be considered at a relatively low reaction temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a composite catalyst and a preparation method and application thereof. Background Art

[0002] With the rapid development of human society and the continuous progress of science and technology, the contradiction between energy supply and demand has become increasingly prominent. How to effectively develop sustainable energy to ensure energy supply is a major problem that human society urgently needs to solve. Fischer-Tropsch synthesis (CO hydrogenation) can effectively convert synthesis gas from non-petroleum carbon resources into liquid fuels and high-value chemicals, providing an important implementation approach to solving the energy crisis. However, under normal circumstances, the product distribution of Fischer-Tropsch synthesis is constrained by the traditional ASF distribution model. Except for methane, the selectivity of each target product has a maximum value, among which low-carbon hydrocarbons (C 2-4 )、Gasoline(C 5-11 ), kerosene (C 8-16 ) and diesel (C 11-20 ) are 58%, 48%, 41% and 40% respectively. If the selectivity of each target product cannot be effectively improved, it will put tremendous pressure on the subsequent separation and upgrading process, and will not be conducive to the efficient operation of the Fischer-Tropsch reaction itself. Compared with gasoline and diesel, the carbon number of the jet fuel fraction is in the middle. How to achieve a balance between high jet fuel selectivity and low methane selectivity has always been a difficult point in research.

[0003] For many years, researchers have been committed to optimizing the selectivity of Fischer-Tropsch synthesis products through the rational construction of catalysts. Li et al. used Y-type zeolite as a carrier to load cobalt nanoparticles, and successfully achieved the regulation of product selectivity by adjusting the acidity and pore structure of mesoporous Y-type zeolite, reaching 74%, 72% and 58% for gasoline, jet fuel and diesel fractions, respectively (Nat. Catal. 2017, 1(10): 787-793). Wang et al. synthesized ZSM-5 zeolites with different acidity and mesoporous pore volume by changing the concentration of TPAOH solution, and then loaded CoMn as an active component. It was found that the zeolite treated with 0.5 M TPAOH solution had the largest mesoporous pore volume and suitable Brønsted acidity, which could achieve a selectivity of up to 50% for jet fuel (Ind. Eng. Chem. Res. 2021, 60, 5783-5791). Yang et al. prepared Y-modified β molecular sieves by ion exchange and found that Co / Y-β catalysts with a suitable ratio of Y can exhibit a jet fuel selectivity of 41.2% (Sustain. Energy Fuels 2020,4 (7): 3528-3536). Cai et al. prepared SBA-15 molecular sieves with different Al / Si ratios and found that when Al / Si was 0.01, the jet fuel selectivity of cobalt-based catalysts could be as high as 52.4% (Ind. Eng. Chem. Res. 2018, 57, 3844−3854). Based on the results of existing literature, the high-selectivity jet fuel preparation technology of Fischer-Tropsch synthesis still has the inherent defects of being difficult to achieve both high CO conversion rate and high jet fuel selectivity, and the reaction temperature is relatively high (250-260°C). How to achieve high-selectivity synthesis of jet fuel at low temperature requires further research. Summary of the invention

[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a composite catalyst and its preparation method and application. The composite catalyst provided by the present invention is used in Fischer-Tropsch synthesis, which can achieve both high CO conversion rate and high jet fuel selectivity at a lower reaction temperature. In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a composite catalyst, which includes a molecular sieve and a cobalt-based catalyst. Based on the total amount of the composite catalyst, the content of the molecular sieve is 2-35wt%, and the content of the cobalt-based catalyst is 65-98wt%. The cobalt-based catalyst includes zirconium oxide and cobalt. Based on the total amount of the cobalt-based catalyst, the content of the cobalt element is 5-35wt%, and the content of zirconium oxide is 65-95wt%; based on the total amount of zirconium oxide, the content of zirconium oxide in the monoclinic phase is more than 50%.

[0005] Preferably, the molecular sieve is a β molecular sieve.

[0006] The second aspect of the present invention provides a method for preparing the composite catalyst, which comprises: mixing the molecular sieve and the cobalt-based catalyst, grinding them, and then molding them, or molding and crushing the molecular sieve and the cobalt-based catalyst separately, and then mixing them.

[0007] A third aspect of the present invention provides the use of the composite catalyst in a Fischer-Tropsch synthesis reaction, preferably in a Fischer-Tropsch synthesis reaction for producing jet fuel.

[0008] The present invention obtains a composite catalyst by mixing a supported cobalt-based catalyst and a molecular sieve, and effectively realizes high-selectivity preparation of jet fuel at 220°C. By adjusting the composite ratio and method, the ratio, proximity and synergistic mechanism of metal active sites and acid sites can be effectively changed, which is beneficial to changing the secondary isomerization cracking effect of heavy hydrocarbon products, so that the catalyst exhibits excellent jet fuel fraction selectivity. The composite catalyst provided by the present invention is a highly potential catalyst for high-selectivity preparation of jet fuel. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 It is the XRD spectra of zirconium oxide in Example 1, Example 5 and Comparative Example 1. DETAILED DESCRIPTION

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0011] The first aspect of the present invention provides a composite catalyst, which includes a molecular sieve and a cobalt-based catalyst. Based on the total amount of the composite catalyst, the content of the molecular sieve is 2-35wt%, and the content of the cobalt-based catalyst is 65-98wt%. The cobalt-based catalyst includes zirconium oxide and cobalt. Based on the total amount of the cobalt-based catalyst, the content of the cobalt element is 5-35wt%, and the content of zirconium oxide is 65-95wt%. Based on the total amount of zirconium oxide, the content of zirconium oxide in the monoclinic phase is more than 50%.

[0012] In the present invention, the contents of molecular sieve, cobalt and zirconium oxide are measured by XRF method. The type of molecular sieve is determined by X-ray diffraction (XRD) characterization.

[0013] In the present invention, the crystal form of the zirconium oxide can be determined by X-ray diffraction (XRD) characterization. In the XRD spectrum of standard monoclinic zirconium oxide (m-ZrO2), the characteristic diffraction peaks at 2θ of 24.1°, 27.9°, and 31.4° can be respectively attributed to (110), (27.9°, and (31.4°) of m-ZrO2. , (111) crystal plane (JCPDS 001-0750); in the XRD spectrum of standard tetragonal zirconium oxide (t-ZrO2), the characteristic diffraction peaks at 2θ of 30.5°, 35.6°, 51.0°, and 60.5° can be attributed to the (101), (110), (200), and (211) crystal planes of t-ZrO2, respectively (JCPDS 002-0733). ×100%, the content of monoclinic zirconia is calculated ( X m ).in, and Represents m-ZrO2 in XRD spectrum and the fitting intensity (fitting peak area) of the (111) crystal plane, Represents the fitting intensity (fitting peak area) of the t-ZrO2 (101) crystal plane in the XRD spectrum.

[0014] According to a preferred embodiment of the present invention, based on the total amount of the composite catalyst, the content of the molecular sieve is 10-20wt%, and the content of the cobalt-based catalyst is 80-90wt%. The use of this preferred embodiment is more conducive to making the catalyst have both high CO conversion rate and aviation kerosene fraction selectivity. When the molecular sieve content is low, the heavy hydrocarbon content in the Fischer-Tropsch reaction product is high, and the aviation kerosene fraction selectivity is low. When the molecular sieve content is high, the cobalt-based active sites are likely to be covered by the molecular sieve, resulting in a significant decrease in CO conversion rate.

[0015] Preferably, the total acid amount of the composite catalyst is 50-400 μmol / g, more preferably 100-300 μmol / g. In the present invention, the total acid amount of the composite catalyst is measured by ammonia temperature programmed desorption NH3-TPD. Specifically, 200 mg of a 40-60 mesh sample is weighed and placed in a reaction tube. The temperature is raised to 400°C at a heating rate of 10°C / min and maintained for 2h in a high-purity He atmosphere. The pretreatment process is to remove water and other impurities adsorbed on the surface. Subsequently, the temperature is lowered to 100°C, and the atmosphere is switched to NH3 / He mixed gas (NH3 volume ratio is 5%) for pulse adsorption to saturation. Finally, the atmosphere is switched back to He gas purge, and after the baseline is stable, the temperature is raised to 600°C at a heating rate of 10°C / min to collect data.

[0016] There is no particular limitation on the shape of the composite catalyst, as long as it satisfies the above composition, and it can be adaptively selected according to specific application occasions. Preferably, the composite catalyst is a granular catalyst with a particle size of 20-40 meshes.

[0017] The present invention has a wide range of selection for the type of the molecular sieve. Preferably, the molecular sieve is at least one of β molecular sieve, Y molecular sieve and ZSM-5 molecular sieve, and more preferably β molecular sieve. The inventors of the present invention found in the research process that combining β molecular sieve with the cobalt-based catalyst is more conducive to improving the CO conversion rate and jet fuel selectivity of the composite catalyst under low temperature conditions.

[0018] Preferably, the SiO2 / Al2O3 molar ratio of the molecular sieve is 3-200, more preferably 10-90.

[0019] Preferably, the molecular sieve is a Y molecular sieve, and the SiO2 / Al2O3 molar ratio of the Y molecular sieve is 4-10.

[0020] Preferably, the molecular sieve is a ZSM-5 molecular sieve, and the SiO2 / Al2O3 molar ratio of the ZSM-5 molecular sieve is 30-150.

[0021] Preferably, the molecular sieve is a β molecular sieve, the β molecular sieve is an all-silicon molecular sieve, or its SiO2 / Al2O3 molar ratio is 10-90, more preferably 20-80.

[0022] According to a preferred embodiment of the present invention, the mesopore volume of the β molecular sieve accounts for 20-100% of the total pore volume, preferably 30-60%.

[0023] The mesopore volume and total pore volume of the beta molecular sieve are obtained by nitrogen physical adsorption and desorption test.

[0024] According to a preferred embodiment of the present invention, the medium-strong acid content of the β molecular sieve is 200-850 μmol / g, preferably 500-700 μmol / g.

[0025] The medium-strong acid content of the beta molecular sieve is obtained by NH3-TPD test. Specifically, 200 mg of 40-60 mesh sample is weighed and placed in a reaction tube. The temperature is raised to 400°C at a heating rate of 10°C / min and maintained for 2h in a high-purity He atmosphere. The pretreatment process is to remove water and other impurities adsorbed on the surface. Then the temperature is lowered to 100°C, and the atmosphere is switched to NH3 / He mixed gas (NH3 volume ratio is 5%) for pulse adsorption to saturation. Finally, the atmosphere is switched back to He gas purge, and after the baseline is stable, the temperature is raised to 600°C at a heating rate of 10°C / min to collect data. The medium-strong acid content can be calculated from the high-temperature desorption peak (desorption temperature is greater than 300°C) after the NH3-TPD spectrum is separated.

[0026] According to a preferred embodiment of the present invention, the specific surface area of ​​the beta molecular sieve is 400-800 m 2 / g, preferably 450-650 m 2 / g.

[0027] In the present invention, the specific surface area is obtained by nitrogen physical adsorption and desorption test.

[0028] The present invention adopts the above-mentioned beta molecular sieve with specific mesopore volume ratio, specific surface area and medium-strong acid content in combination with a cobalt-based catalyst, which is more conducive to promoting the diffusion and secondary reaction of intermediate species and products, thereby effectively improving the selectivity of aviation fuel fraction.

[0029] The present invention has no particular limitation on the source of the molecular sieve, which can be purchased commercially or prepared by existing methods.

[0030] According to a preferred embodiment of the present invention, based on the total amount of the cobalt-based catalyst, the content of cobalt element is 16-30wt%, for example, it can be 16wt%, 18wt%, 20 wt%, 22wt%, 24 wt%, 26wt%, 28 wt%, 30wt%; the content of zirconium oxide is 70-84wt%, for example, it can be 70wt%, 72wt%, 74wt%, 76wt%, 78wt%, 80 wt%, 82wt%, 84wt%.

[0031] According to the present invention, it is preferred that the cobalt-based catalyst consists of zirconium oxide and active component cobalt.

[0032] The present invention has no particular limitation on the form of the cobalt; it may exist in an oxidized form, a reduced form, or a partially oxidized form and a partially reduced form. Cobalt catalysts in different forms are all within the protection scope of the present invention.

[0033] In the present invention, preferably, based on the total amount of zirconium oxide, the content of zirconium oxide in the monoclinic phase is 70-100%. This preferred embodiment is more conducive to improving the CO conversion rate and aviation kerosene selectivity of the composite catalyst.

[0034] According to a preferred embodiment of the present invention, the method for preparing the cobalt-based catalyst comprises the following steps: (1) Zirconium oxide is prepared by a hydrothermal method; (2) A cobalt precursor is introduced into the zirconium oxide by an impregnation method, followed by drying and calcining.

[0035] The present invention has no particular limitation on the method of preparing zirconium oxide by the hydrothermal method in step (1), as long as the above-mentioned crystalline zirconium oxide can be obtained. Preferably, step (1) comprises: reacting a zirconium salt precursor solution and a precipitant under hydrothermal conditions, followed by drying and calcining.

[0036] Preferably, the zirconium salt precursor includes at least one of zirconium nitrate, zirconium oxynitrate, zirconium oxychloride, zirconium chloride and zirconium acetate. The embodiment of the present invention is described by taking zirconium oxynitrate as an example, but the present invention is not limited thereto.

[0037] According to the present invention, preferably, the solvent in the zirconium salt precursor solution includes water and optionally alcohol, and the water content is 90-100% by volume based on the total amount of the solvent. By controlling the water content in the solvent, it is more conducive to obtaining a catalyst with improved performance.

[0038] The present invention has a wide selection range for the alcohol, and various conventionally used alcohols can be used in the present invention, such as C1-C5 alcohols, including but not limited to methanol, ethanol or propanol, preferably methanol.

[0039] Preferably, the precipitant is selected from at least one of urea, ammonia water, ammonium carbonate and hexadecyltrimethylammonium chloride, more preferably urea.

[0040] According to the present invention, preferably, the molar ratio of the precipitant to the zirconium salt precursor is 3-30, preferably 8-12.

[0041] According to the present invention, preferably, the hydrothermal conditions include: a hydrothermal temperature of 100-250°C, preferably 120-200°C; a hydrothermal time of 10-30 hours, preferably 20-24 hours. The hydrothermal conditions of this preferred embodiment are more conducive to obtaining zirconium oxide with perfect crystal form and more conducive to improving the Fischer-Tropsch synthesis performance of the catalyst.

[0042] According to the present invention, the hydrothermal reaction is carried out under closed conditions. The present invention has no particular limitation on the equipment for carrying out the hydrothermal reaction, for example, it can be a hydrothermal kettle, including but not limited to a polytetrafluoroethylene liner of a stainless steel hydrothermal kettle, which is sealed and placed in an oven.

[0043] Preferably, the calcination conditions in step (1) include: a calcination temperature of 300-700°C, preferably 400-500°C; a calcination time of 2-10 hours, preferably 3-8 hours; a calcination heating rate of 1-5°C / min, and the preferred atmosphere is air, nitrogen or argon.

[0044] According to the present invention, preferably, before the calcination in step (1), the hydrothermal reaction product is further washed and dried. The washing and drying methods and conditions can be carried out according to conventional technical means in the art. Preferably, in the washing method, after the hydrothermal reaction is completed, the supernatant is poured out and the precipitate is repeatedly washed with water and ethanol for multiple times, for example, 2-10 times. Preferably, the drying method is forced air drying or vacuum drying; the drying temperature is 50-150°C, preferably 80-120°C; the drying time is 4-48 hours, preferably 8-16 hours.

[0045] According to the present invention, preferably, the method further comprises, after the drying in step (1), grinding the dried product and then performing the roasting.

[0046] By controlling the solvent, hydrothermal reaction conditions, precipitant and zirconium precursor ratio in the above-mentioned zirconium oxide process, the type and ratio of zirconium oxide crystal phases can be effectively controlled, so that the obtained catalyst has better Fischer-Tropsch synthesis performance.

[0047] In the present invention, there is no particular limitation on the impregnation method, and it can be equal volume impregnation or excess impregnation, and is preferably equal volume impregnation.

[0048] According to a preferred embodiment of the present invention, the method of introducing the cobalt precursor into the zirconium oxide by the impregnation method specifically comprises: impregnating the zirconium oxide with an impregnation solution containing the cobalt precursor, and then performing the drying and calcining in step (2).

[0049] The present invention has no particular limitation on the type of the cobalt precursor. Preferably, the cobalt precursor is selected from at least one of cobalt nitrate, cobalt acetate and cobalt chloride.

[0050] Those skilled in the art may select the concentration of the impregnation solution containing the cobalt precursor according to the target cobalt content.

[0051] The present invention has a wide range of selection for the drying method and conditions of step (2). Preferably, the drying method is forced air drying or vacuum drying, the drying temperature is 50-150°C, preferably 80-120°C; the drying time is 4-48 hours, preferably 8-16 hours.

[0052] According to the present invention, preferably, the calcination conditions in step (2) include: a calcination temperature of 300-500°C, preferably 350-450°C; a calcination time of 2-8 hours, preferably 4-6 hours; a calcination heating rate of 1-5°C / min; and preferably an atmosphere of air, nitrogen, argon or nitric oxide.

[0053] In the present invention, the calcination in step (1) and step (2) can be carried out independently in a tube furnace or a muffle furnace.

[0054] According to a preferred embodiment of the present invention, the calcination temperature during the preparation of zirconium oxide (i.e., the calcination temperature described in step (1)) does not exceed 500°C, and the calcination temperature after loading cobalt (i.e., the calcination temperature described in step (2)) is not higher than the calcination temperature during the preparation of zirconium oxide. More preferably, the calcination temperature during the preparation of zirconium oxide is 400-500°C, and the calcination temperature after loading cobalt is 0-100°C lower than the calcination temperature during the preparation of zirconium oxide. The preferred method of carrier calcination conditions can ensure the stability of the carrier zirconium oxide crystal phase and pore structure, and the preferred method of calcination conditions after loading cobalt can ensure the stability of the carrier after loading cobalt. If the above preferred range is not met, for example, if the calcination temperature of the carrier is too high, it will cause the collapse of the pore structure and a significant decrease in the specific surface area, thereby affecting the subsequent dispersion of cobalt. If the calcination temperature after loading cobalt is too high, it will destroy the carrier structure and cause the cobalt particles to agglomerate.

[0055] The present invention has no particular limitation on the preparation method of the composite catalyst, and various methods conventionally used in the art can be used. The present invention provides a method for preparing the composite catalyst described in the first aspect, which comprises: grinding after mixing the molecular sieve and the cobalt-based catalyst, and then forming, or respectively forming and crushing the molecular sieve and the cobalt-based catalyst, and then mixing. Preferably, the method for preparing the composite catalyst comprises: grinding after mixing the molecular sieve and the cobalt-based catalyst, and then forming. In this preferred embodiment, the molecular sieve and the cobalt-based catalyst are mixed, and then ground and formed together, which is more conducive to the effective contact between the metal active site and the molecular sieve acid site, so as to be more conducive to improving the CO conversion rate and jet fuel selectivity of the prepared composite catalyst.

[0056] According to a specific embodiment of the present invention, the preparation method includes: mixing molecular sieve powder and cobalt-based catalyst powder in a certain proportion, grinding (which can be done in a mortar or ball mill) evenly, then molding and crushing, and finally screening to obtain a composite catalyst with a particle size that meets the requirements.

[0057] In the method provided by the present invention, the molding can be various molding methods conventionally used in the art, such as tablet molding, extrusion molding, preferably tablet molding.

[0058] According to another specific embodiment of the present invention, the preparation method comprises: molding, crushing and sieving the molecular sieve powder and the cobalt-based catalyst powder respectively, and then physically mixing the two particles of the same mesh size in a certain proportion to obtain a composite catalyst.

[0059] According to a preferred embodiment of the present invention, the preparation method of the composite catalyst further comprises a reduction step. The reduction is to reduce the cobalt-based catalyst. It can be carried out during the preparation process of the cobalt-based catalyst, that is, in step (2), a cobalt precursor is introduced into the zirconium oxide by an impregnation method, and then dried and calcined, and then reduced. It can also be reduced after mixing with a molecular sieve. Preferably, the reduction is carried out after mixing with a molecular sieve.

[0060] According to a preferred embodiment of the present invention, preferably, the reduction conditions include: under a hydrogen-containing atmosphere, the reduction temperature is 300-500 ° C, preferably 400-450 ° C, the pressure is 0.1-1MPa, preferably 0.1-0.5MPa, and the time is 3-15 hours, preferably 5-10 hours. More preferably, the hydrogen-containing atmosphere is a pure hydrogen atmosphere.

[0061] According to the present invention, preferably, the reduction temperature of the cobalt-based catalyst or composite catalyst is not lower than 350°C, and is not higher than the calcination temperature after loading cobalt in the preparation process of the cobalt-based catalyst, preferably 0-50°C lower. This preferred embodiment is more conducive to improving the CO conversion rate and jet fuel selectivity of the catalyst.

[0062] The third aspect of the present invention provides the use of the composite catalyst in a Fischer-Tropsch synthesis reaction, preferably in a Fischer-Tropsch synthesis reaction to produce jet fuel. The composite catalyst provided by the present invention is used in a Fischer-Tropsch synthesis reaction to increase CO conversion and jet fuel selectivity.

[0063] The present invention has no particular limitation on the composition of the jet fuel, and there are conventional schematics, for example, the number of carbon atoms in the jet fuel is 8-16.

[0064] Preferably, the conditions of the Fischer-Tropsch synthesis reaction include: a H2 / CO volume ratio of 1-2 in the reaction feed gas, a reaction temperature of 200-250°C, preferably 210-230°C, a reaction pressure of 1.5-4MPa, and a reaction volume space velocity of 1000-10000 h -1 The composite catalyst provided by the present invention can reduce the temperature of the Fischer-Tropsch synthesis reaction to a certain extent, for example, it can achieve high selectivity in the preparation of jet fuel at 220°C.

[0065] The present invention will be described in detail below through examples.

[0066] In the following examples and comparative examples, the crystal form of the zirconium oxide and the content of each crystal form are determined by X-ray diffraction (XRD) characterization. The total acid content of the composite catalyst is determined by NH3-TPD. The mesoporous pore volume and total pore volume of the molecular sieve are obtained by nitrogen physical adsorption and desorption test. The medium-strong acid content of the molecular sieve is obtained by NH3-TPD test. The specific test conditions are as described in the above specific implementation method part and will not be repeated here.

[0067] The contents of molecular sieve, cobalt and zirconium oxide are calculated by feed ratio.

[0068] Example 1 (1) Preparation of carrier zirconium oxide: Weigh 7.376 g of zirconium oxynitrate, dissolve it in 150 mL of deionized water, stir evenly, then add 15.4 g of urea, stir the mixed solution evenly, pour it into a 200 mL polytetrafluoroethylene liner, seal the stainless steel reactor, put it into an oven, and heat it at 160 °C for 24 hours. After the reactor cools down, pour out the supernatant, wash the precipitate repeatedly with water and ethanol for more than 5 times, and put it into a blast oven to dry at 120 °C for 12 hours. After the dried powder is ground, it is placed in a muffle furnace for calcination, air is introduced, and the temperature is raised to 400 °C at a rate of 2 °C / min. It is calcined at 400 °C for 3 hours to obtain a carrier named Z1. Its XRD spectrum is shown as follows Figure 1 As shown, from Figure 1 It can be seen that pure monoclinic zirconia can be obtained by using pure water as solvent.

[0069] (2) Preparation of supported cobalt-based catalyst: Take 2 g of Z1 and measure its water absorption. Then calculate the amount of cobalt nitrate and deionized water according to the water absorption and cobalt loading (16 wt%). Add the prepared cobalt nitrate solution dropwise into Z1. After rotary evaporation of excess solvent, dry it in an oven at 120 °C, place it in a tubular furnace, let air in, and heat it to 400 °C at a rate of 2 °C / min. Hold for 4 h to obtain the C1 catalyst.

[0070] (3) Preparation of composite catalyst: C1 powder and β molecular sieve (properties shown in Table 1) powder were physically mixed in a mass ratio of 9 / 1, ground evenly in a mortar, and then tableted and crushed and sieved into 20-40 mesh to obtain the final catalyst named M1. The total acid content of the composite catalyst is listed in Table 1.

[0071] Example 2 (1) Preparation of carrier zirconium oxide: same as in Example 1.

[0072] (2) Preparation of supported cobalt-based catalyst: Take 2 g of Z1 and measure its water absorption. Then calculate the amount of cobalt nitrate and deionized water according to the water absorption and cobalt loading (25 wt%). Add the prepared cobalt nitrate solution dropwise into Z1. After rotary evaporation of excess solvent, dry it in an oven at 120 °C, place it in a tubular furnace, let air in, and heat it to 400 °C at a rate of 2 °C / min. Hold for 4 h to obtain the C2 catalyst.

[0073] (3) Preparation of composite catalyst: C2 powder and β molecular sieve (properties shown in Table 1) powder were physically mixed in a mass ratio of 4 / 1, ground evenly in a mortar, and then tableted and crushed and sieved into 20-40 mesh to obtain the final catalyst named M2. The total acid content of the composite catalyst is listed in Table 1.

[0074] Example 3 C1 was prepared according to the method of Example 1, except that C1 powder and β molecular sieve powder were mixed in a mass ratio of 2 / 1. The obtained catalyst was named M3.

[0075] Example 4 C1 was prepared according to the method of Example 1, except that C1 powder and β molecular sieve powder were respectively tableted and crushed and sieved to obtain two kinds of particles with a mesh size of 20-40, and then the two kinds of particles were physically mixed in a mass ratio of 9 / 1 to obtain the final catalyst M4.

[0076] Example 5 (1) Preparation of carrier zirconium oxide: The method of Example 1 was followed, except that a mixed solution (water and methanol in a volume ratio of 10 / 90) was used for hydrothermal treatment. The carrier was named Z2, and its XRD spectrum was as follows: Figure 1 As shown, from Figure 1 It can be seen that Z2 has characteristic diffraction peaks of both monoclinic and tetragonal zirconium oxide. Calculation shows that the proportion of the monoclinic phase is 70.4%.

[0077] (2) Preparation of supported cobalt-based catalyst: Take 2 g of Z2 and measure its water absorption. Then calculate the amount of cobalt nitrate and deionized water according to the water absorption and cobalt loading (16 wt%). Add the prepared cobalt nitrate solution dropwise into Z2. After rotary evaporation of excess solvent, dry it in an oven at 120 °C, put it in a tubular furnace, let air in, and heat it to 400 °C at a rate of 2 °C / min. Hold it for 4 h to obtain the C3 catalyst.

[0078] (3) Preparation of composite catalyst: C3 powder and β molecular sieve (properties see Table 1) powder were physically mixed in a mass ratio of 9 / 1, ground evenly in a mortar, and then tableted and crushed and sieved into 20-40 mesh to obtain the final catalyst named M5.

[0079] Example 6 The method of Example 1 was followed, except that the β molecular sieve was replaced with an equal mass of HY molecular sieve. The resulting catalyst was named M6.

[0080] Comparative Example 1 (1) Preparation of carrier zirconium oxide: Weigh 7.376 g of zirconium oxynitrate, dissolve it in 150 mL of methanol, stir evenly, then add 15.4 g of urea, stir the mixed solution evenly, pour it into a 200 mL polytetrafluoroethylene liner, seal the stainless steel reactor, put it in an oven, and hydroheat it at 160 °C for 24 hours. After the reactor cools down, pour out the supernatant, wash the precipitate repeatedly with water and ethanol for more than 5 times, and put it in a blast oven to dry at 120 °C for 12 hours. After the dried powder is ground, it is placed in a muffle furnace for calcination, air is introduced, and the temperature is raised to 400 °C at a rate of 2 °C / min. It is calcined at 400 °C for 3 hours to obtain a carrier named Z3, and its XRD spectrum is shown as follows Figure 1 As shown, from Figure 1 It can be seen that pure tetragonal zirconia is prepared using pure methanol solvent.

[0081] (2) Preparation of supported cobalt-based catalyst: Take 2 g of Z3 and measure its water absorption. Then calculate the amount of cobalt nitrate and deionized water according to the water absorption and cobalt loading (16 wt%). Add the prepared cobalt nitrate solution dropwise into Z3. After rotary evaporation of excess solvent, dry it in an oven at 120 °C, put it in a tubular furnace, let air in, and heat it to 400 °C at a rate of 2 °C / min. Hold it for 4 h to obtain the C4 catalyst.

[0082] (3) Preparation of composite catalyst: C4 powder and β molecular sieve (properties shown in Table 1) powder were physically mixed in a mass ratio of 9 / 1, ground evenly in a mortar, and then tableted and crushed and sieved into 20-40 mesh to obtain the final catalyst named M7. The total acid content of the composite catalyst is listed in Table 1.

[0083] Table 1

[0084] Test Case The performance of the catalysts prepared in the above examples and comparative examples was evaluated.

[0085] The cobalt-based catalyst in the catalyst prepared in the embodiment and the comparative example is used as the calculation basis. According to the amount of cobalt-based catalyst, 20-40 mesh catalyst is taken, and it is mixed with quartz sand at a ratio of 1:10, and then loaded into a fixed bed reactor. The inner diameter of the reaction tube used is 18 mm, and the length of the constant temperature zone is 40 mm. The catalyst is then reduced in situ, the gas is pure hydrogen, the reduction temperature is 400°C, the pressure is 0.1MPa, and the reduction time is 10 hours; the H2 / CO volume ratio in the Fischer-Tropsch reaction feed gas is 2, the reaction temperature is 220°C, the reaction pressure is 2 MPa, and the reaction volume space velocity (based on the cobalt-based catalyst) is 4800 h -1 The raw gas and the reaction gas phase products were analyzed online by Agilent 7890A gas chromatograph, and the liquid phase products were collected by hot trap and cold trap, separated, weighed and then analyzed offline. All performance evaluation results are shown in Table 2.

[0086] Table 2 Fischer-Tropsch performance of composite catalysts

[0087] As can be seen from the data in Table 2, the jet fuel selectivity of Examples 1-3 is as high as 59-62%, indicating that the addition of molecular sieves can effectively regulate the secondary cracking of heavy hydrocarbons to generate intermediate fractions, but in Example 3, the molecular sieve content is 33%, which may affect the contact between the active sites and the reactant molecules in the cobalt-based catalyst, thereby significantly reducing its selectivity. The CO conversion rate and jet fuel selectivity in the performance tested by particle mixing in Example 4 are significantly lower than those of the powder mixed catalyst, indicating that the contact mode of the molecular sieve and the metal catalyst in the composite catalyst will have a greater impact on the catalytic performance. This is because the proximity of the acid sites on the molecular sieve and the metal active sites of the metal catalyst will affect the secondary reaction of the intermediate product. If the distance between the two sites increases when the particles are mixed, it is not conducive to the generation of intermediate fractions. Compared with β molecular sieves, the medium and strong acid content of HY molecular sieves is significantly reduced, and the mesopore ratio is low, which is not conducive to the cracking and diffusion of intermediate species. Therefore, at a lower reaction temperature, Example 6 presents a poor CO conversion rate and jet fuel selectivity. When pure methanol is used as the solvent, pure tetragonal zirconia is obtained. The catalyst shows a relatively low CO conversion rate, indicating that using tetragonal zirconia as a carrier is not conducive to improving the performance of the Fischer-Tropsch reaction.

[0088] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite catalyst, characterized in that: The composite catalyst includes molecular sieve and cobalt-based catalyst. Based on the total amount of the composite catalyst, the content of the molecular sieve is 2-35wt%, and the content of the cobalt-based catalyst is 65-98wt%. The cobalt-based catalyst includes zirconium oxide and cobalt. Based on the total amount of the cobalt-based catalyst, the content of the cobalt element is 5-35wt%, and the content of zirconium oxide is 65-95wt%. Based on the total amount of zirconium oxide, the content of zirconium oxide in the form of monoclinic phase is above 50%.

2. The composite catalyst according to claim 1, wherein Based on the total amount of the composite catalyst, the content of the molecular sieve is 10-20wt%, and the content of the cobalt-based catalyst is 80-90wt%; Preferably, the total acid amount of the composite catalyst is 50-400 μmol / g, more preferably 100-300 μmol / g; Preferably, the composite catalyst is a granular catalyst with a particle size of 20-40 meshes.

3. The composite catalyst according to claim 1, wherein The molecular sieve is at least one selected from β molecular sieve, Y molecular sieve and ZSM-5 molecular sieve, more preferably β molecular sieve; Preferably, the SiO2 / Al2O3 molar ratio of the molecular sieve is 3-200, more preferably 10-90.

4. The composite catalyst according to claim 3, wherein The mesopore volume of the β molecular sieve accounts for 20-100% of the total pore volume, preferably 30-60%; and / or, the medium-strong acid content of the beta molecular sieve is 200-850 μmol / g, preferably 500-700 μmol / g; And / or, the specific surface area of ​​the beta molecular sieve is 400-800 m 2 / g, preferably 450-650 m 2 / g; And / or, the β molecular sieve is an all-silicon molecular sieve, or its SiO2 / Al2O3 molar ratio is 20-80.

5. The composite catalyst according to any one of claims 1 to 4, wherein Based on the total amount of the cobalt-based catalyst, the content of cobalt element is 16-30wt%, and the content of zirconium oxide is 70-84wt%; And / or, based on the total amount of zirconium oxide, the content of zirconium oxide in the monoclinic phase is 70-100%.

6. The composite catalyst according to any one of claims 1 to 5, wherein The preparation method of the cobalt-based catalyst comprises the following steps: (1) Zirconium oxide is prepared by a hydrothermal method; (2) A cobalt precursor is introduced into the zirconium oxide by an impregnation method, followed by drying and calcining.

7. The composite catalyst according to claim 6, wherein Step (1) comprises: reacting a zirconium salt precursor solution and a precipitant under hydrothermal conditions, followed by drying and calcining; Preferably, the zirconium salt precursor includes at least one of zirconium nitrate, zirconium oxynitrate, zirconium oxychloride, zirconium chloride and zirconium acetate; Preferably, the solvent in the zirconium salt precursor solution includes water and optionally alcohol, and the water content is 90-100% by volume based on the total amount of the solvent; Preferably, the precipitant is selected from at least one of urea, ammonia water, ammonium carbonate and hexadecyltrimethylammonium chloride; Preferably, the molar ratio of the precipitant to the zirconium salt precursor is 3-30, preferably 8-12; Preferably, the hydrothermal conditions include: hydrothermal temperature of 100-250 ° C, preferably 120-200 ° C; hydrothermal time of 10-30 hours, preferably 20-24 hours; Preferably, the drying conditions include forced air drying or vacuum drying, the drying temperature is 50-150°C, preferably 80-120°C; the drying time is 4-48 hours, preferably 8-16 hours; Preferably, the calcination conditions in step (1) include: a calcination temperature of 300-700°C, preferably 400-500°C; a calcination time of 2-10 hours, preferably 3-8 hours; a calcination heating rate of 1-5°C / min, and the preferred atmosphere is air, nitrogen or argon.

8. The composite catalyst according to claim 6, wherein The calcination conditions in step (2) include: a calcination temperature of 300-500°C, preferably 350-450°C; a calcination time of 2-8 hours, preferably 4-6 hours; a calcination heating rate of 1-5°C / min; and a preferred atmosphere of air, nitrogen, argon or nitric oxide.

9. The composite catalyst according to any one of claims 1 to 8, wherein The calcination temperature during the preparation of zirconium oxide does not exceed 500°C, and the calcination temperature after loading cobalt is not higher than the calcination temperature during the preparation of zirconium oxide; Preferably, the calcination temperature during the preparation of zirconium oxide is 400-500° C., and the calcination temperature after loading cobalt is 0-100° C. lower than the calcination temperature during the preparation of zirconium oxide.

10. A method for preparing the composite catalyst according to any one of claims 1 to 9, the method comprising: The molecular sieve and the cobalt-based catalyst are mixed and ground, and then molded, or the molecular sieve and the cobalt-based catalyst are molded and crushed separately, and then mixed.

11. The preparation method according to claim 10, wherein: The preparation method further comprises reducing the obtained composite catalyst; Preferably, the reduction conditions include: under a hydrogen-containing atmosphere, a reduction temperature of 300-500 ° C, preferably 400-450 ° C, a pressure of 0.1-1 MPa, preferably 0.1-0.5 MPa, and a time of 3-15 hours, preferably 5-10 hours; Preferably, the reduction temperature of the composite catalyst is not lower than 350°C and not higher than the calcination temperature after cobalt loading during the preparation of the cobalt-based catalyst, preferably 0-50°C lower.

12. Use of the composite catalyst according to any one of claims 1 to 9 in a Fischer-Tropsch synthesis reaction, preferably in a Fischer-Tropsch synthesis reaction for producing jet fuel; Preferably, the conditions of the Fischer-Tropsch synthesis reaction include: The volume ratio of H2 / CO in the reaction raw gas is 1-2, the reaction temperature is 200-250°C, preferably 210-230°C, the reaction pressure is 1.5-4MPa, and the reaction volume space velocity is 1000-10000 h -1 .

Citation Information

Patent Citations

  • Desulphurization catalyst and preparation method and application thereof

    CN104415775A

  • Cobalt-based catalyst, and preparation method and application thereof, and Fischer-Tropsch synthesis method

    CN108654637A

  • Zirconium-aluminum composite sol, preparation method and applications thereof, and preparation method of catalytic cracking catalyst

    CN110876926A

  • Composite structure carrier low temperature sulfur-tolerant methanation catalyst and preparation method thereof

    CN111266130A

  • Catalytic cracking catalyst for producing low-carbon olefin through hydrocarbon oil conversion

    CN112642475A